2023
DOI: 10.1146/annurev-earth-031920-083456
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Consequences of Solar Geoengineering

Abstract: As atmospheric carbon dioxide concentrations rise and climate change becomes more destructive, geoengineering has become a subject of serious consideration. By reflecting a fraction of incoming sunlight, solar geoengineering could cool the planet quickly, but with uncertain effects on regional climatology, particularly hydrological patterns. Here, we review recent work on projected hydrologic outcomes of solar geoengineering, in the context of a robust literature on hydrological responses to climate change. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 127 publications
1
13
0
Order By: Relevance
“…This disparity significantly contributes to the range of projections concerning both large-scale and regional changes in the water cycle. Therefore, the impact of SAI on regional and extreme precipitation is still very uncertain (Ricke et al, 2023), however our results are consistent with previous studies which suggest that global-mean precipitation is suppressed under SAI compared to that in the target period. Furthermore, there is a greater reduction in the global and tropical precipitation under G6sulfur than under G6controller, potentially impacting the water and food security of many people living in these regions (Wheeler & Von Braun, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This disparity significantly contributes to the range of projections concerning both large-scale and regional changes in the water cycle. Therefore, the impact of SAI on regional and extreme precipitation is still very uncertain (Ricke et al, 2023), however our results are consistent with previous studies which suggest that global-mean precipitation is suppressed under SAI compared to that in the target period. Furthermore, there is a greater reduction in the global and tropical precipitation under G6sulfur than under G6controller, potentially impacting the water and food security of many people living in these regions (Wheeler & Von Braun, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…While the global mean temperatures in G6sulfur and G6controller are, by design, maintained at SSP2‐4.5 levels, global mean precipitation is reduced compared to SSP2‐4.5. Previous studies have shown that SRM exhibits a different hydrological sensitivity to GHG forcings (e.g., Bala et al., 2008; Kleidon et al., 2015; Niemeier et al., 2013) and that changes in both large scale and regional tropospheric circulation (e.g., Cheng et al., 2022; Simpson et al., 2019) and the combined effects of these on the hydrological cycle and regional precipitation are uncertain (Ricke et al., 2023; Tilmes et al., 2013). Our results show that global mean precipitation under both G6 strategies increases at a similar rate to SSP2‐4.5 for the first 20 years of the simulations but subsequently diverge.…”
Section: Changes In Precipitation and Its Driversmentioning
confidence: 99%
“…For SRM, multiple modeling studies reported that for a certain amount of cooling, global precipitation would be reduced more compared to a GHG‐induced increase (Niemeier et al., 2013; Tilmes et al., 2013), leading to what is usually termed as an “overcompensation of precipitation versus temperature.” Thermodynamical changes in the vertical temperature gradient is shown to be one of the reasons behind this, as the forcing from elevated CO 2 cannot be perfectly matched by a reduction in the incoming solar radiation, due to different mechanisms as the former warms from the bottom‐up, and the latter cools from the top‐down (Govindasamy et al., 2003; Ricke et al., 2023). Other reasons include the contribution of the aerosol‐induced stratospheric heating under SAI (Simpson et al., 2019; Visioni et al., 2021a) or differences between the land response to shortwave versus longwave forcing (Niemeier et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, in 2021 scientists modelled the impact of injecting aerosols over the Indian Ocean to increase rainfall in the semiarid Sahel region of North Africa, which frequently suffers droughts. However, the intervention just shifted the droughts to a different set of nations in East Africa [9] . There's also a risk that stratospheric aerosol injection could shift incidences of malaria from highland areas in East Africa, where the mosquito currently thrives, to lowland areas in South Asia and sub-Saharan Africa [10] .…”
Section: Climate Changementioning
confidence: 99%